2012
DOI: 10.1093/neuonc/nos070
|View full text |Cite
|
Sign up to set email alerts
|

Response assessment in recurrent glioblastoma treated with irinotecan-bevacizumab: comparative analysis of the Macdonald, RECIST, RANO, and RECIST + F criteria

Abstract: Traditionally, the most widely used criteria for response assessment in glioblastoma have been Macdonald and the Response Evaluation Criteria In Solid Tumors (RECIST). Recently, new criteria addressing contrast enhancement and fluid-attenuated inversion recovery (FLAIR)/T2 hyperintensity have been defined (the Response Assessment in Neuro-Oncology criteria) to better evaluate the effect of antiangiogenic therapy. Whether FLAIR/T2 imaging could also be helpful to refine RECIST criteria remains unresolved. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 20 publications
2
58
0
1
Order By: Relevance
“…2). A prior, single-institution retrospective study by Perez-Larraya and colleagues assessing 78 patients with recurrent glioblastoma treated by bevacizumab did not observe a significant difference in PFS between the two criteria, although the use of RANO trended towards a shorter PFS (19). The value of earlier detection of nonenhancing radiographic progression needs to be evaluated in the context of residual survival benefit.…”
Section: Discussionmentioning
confidence: 95%
“…2). A prior, single-institution retrospective study by Perez-Larraya and colleagues assessing 78 patients with recurrent glioblastoma treated by bevacizumab did not observe a significant difference in PFS between the two criteria, although the use of RANO trended towards a shorter PFS (19). The value of earlier detection of nonenhancing radiographic progression needs to be evaluated in the context of residual survival benefit.…”
Section: Discussionmentioning
confidence: 95%
“…MRI partially evaluates tumor infiltration, especially if neoangiogenesis is not widely developed. It remains important to perform MRI T2 FLAIR sequences, using both RECIST and RANO criteria, to assess as accurately as possible responses to treatment with BVZ [22]. To date, no biological marker can identify long-term responders to BVZ.…”
Section: Discussionmentioning
confidence: 99%
“…27 In up to 40% of cases, nonenhancing tumor progression, better appreciated with T2/fluid attenuation inversion recovery (FLAIR) images, may precede the appearance of eventual recurrent contrast-enhancing tumor. [28][29][30][31] However, it remains unclear how to incorporate quantitative assessments of these T2/FLAIR changes into determinations of disease progression. 9,13,32 Multiple studies have shown that although antiangiogenic agents seemed to demonstrate prolonged PFS in patients with recurrent GBM, there seemed to be no significant OS benefit.…”
Section: Pseudoprogressionmentioning
confidence: 99%